Behçet's Syndrome - Yazıcı, Yusuf; Yazıcı, Hasan (Springer New York : Imprint: Springer, 2010)
Behçet's Syndrome has seen great strides over the last 2 decades in the availability of new treatments and the understanding of underlying pathogenesis. Only 30 years ago the majority of particularly young men with Behçet's lost total eye sight, now only a minority do. This book covers the most recent developments in the basic and clinical aspects of Behçet's Syndrome. International authorities have collaborated to offer their diverse expert knowledge on the multiple affected organs and systems, including the skin, the eye, the brain, the lungs and not the least the gastrointestinal and the locomotor systems. A special chapter is devoted to juvenile disease. The definitive resource on Behçet's Syndrome, this book is well suited for rheumatologists, dermatologists, ophthal¬mologists, neurologists, and health professionals caring for Behçet's patients.